Blood-borne biomarkers: CT-DNA ushers in a new era of cancer detection (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Circulating tumor DNA, also called ctDNA, is gaining popularity as a valuable tool for monitoring cancer through non-invasive methods. This review seeks to offer a comprehensive overview of ctDNA, encompassing its biological basis, detection technologies, clinical applications, and challenges. ctDNA originates from tumor cells that undergo apoptosis and necrosis, and contain cancer-specific genomic and epigenomic alterations. Sensitive methodologies leveraging sequencing, digital PCR, and enzymatic assays enable the analysis of mutations, methylation patterns, and copy number variations. ctDNA facilitates early diagnosis, minimal residual disease tracking, therapeutic monitoring, detection of emergent resistance mutations, and prognostic estimates across diverse cancer types. Ongoing trials aim to validate ctDNA's clinical utility and determine whether ctDNA-guided early interventions enhance outcomes. Detection using ctDNA analysis faces some challenges, including specificity, sensitivity, and result interpretation. Research is needed towards advancing the detection technology, development of standards, and establishing clinical validity. Overall, the analysis of plasma ctDNA provides a powerful and minimally invasive avenue for understanding tumor dynamics in real-time to enable personalized therapeutic approaches, monitoring, and potentially early cancer detection.